Absence of Nucleotide-Oligomerization-Domain-2 Is Associated with Less Distinct Disease in Campylobacter jejuni Infected Secondary Abiotic IL-10 Deficient Mice - Heimesaat, Markus M.; Grundmann, Ursula; Alutis, Marie E.; Fischer, André; Bereswill, Stefan (Frontiers in Cellular and Infection Microbiology, 2017)
Human Campylobacter jejuni-infections are progressively increasing worldwide. Despite their high prevalence and socioeconomic impact the underlying mechanisms of pathogen-host-interactions are only incompletely understood. Given that the innate immune receptor nucleotide-oligomerization-domain-2 (Nod2) is involved in clearance of enteropathogens, we here evaluated its role in murine campylobacteriosis. To address this, we applied Nod2-deficient IL-10-/- (Nod2-/- IL-10-/-) mice and IL-10-/- counterparts both with a depleted intestinal microbiota to warrant pathogen-induced enterocolitis. At day 7 following peroral C. jejuni strain 81-176 infection, Nod2 mRNA was down-regulated in the colon of secondary abiotic IL-10-/- and wildtype mice. Nod2-deficiency did neither affect gastrointestinal colonization nor extra-intestinal and systemic translocation properties of C. jejuni. Colonic mucin-2 mRNA was, however, down-regulated upon C. jejuni-infection of both Nod2-/- IL-10-/- and IL-10-/- mice, whereas expression levels were lower in infected, but also naive Nod2-/- IL-10-/- mice as compared to respective IL-10-/- controls. Remarkably, C. jejuni-infected Nod2-/- IL-10-/- mice were less compromised than IL-10-/- counterparts and displayed less distinct apoptotic, but higher regenerative cell responses in colonic epithelia. Conversely, innate as well as adaptive immune cells such as macrophages and monocytes as well as T lymphocytes and regulatory T-cells, respectively, were even more abundant in large intestines of Nod2-/- IL-10-/- as compared to IL-10-/- mice at day 7 postinfection. Furthermore, IFN-γ concentrations were higher in ex vivo biopsies derived from intestinal compartments including colon and mesenteric lymph nodes as well as in systemic tissue sites such as the spleen of C. jejuni infected Nod2-/- IL-10-/- as compared to IL10-/- counterparts. Whereas at day 7 postinfection anti-inflammatory IL-22 mRNA levels were up-regulated, IL-18 mRNA was down-regulated in large intestines of Nod2-/- IL-10-/- versus IL-10-/- mice. In summary, C. jejuni-infection induced less clinical signs and apoptosis, but more distinct colonic pro- and (of note) anti-inflammatory immune as well as regenerative cell responses in Nod2 deficient IL-10-/- as compared to IL-10-/- control mice. We conclude that, even though colonic Nod2 mRNA was down-regulated upon pathogenic challenge, Nod2-signaling is essentially involved in the well-balanced innate and adaptive immune responses upon C. jejuni-infection of secondary abiotic IL-10-/- mice, but does neither impact pathogenic colonization nor translocation.